Comparative health systems research in a context of HIV/AIDS: lessons from a multi-country study in South Africa, Tanzania and Zambia - Veenstra Nina; Dawad Suraya (BMC, 2007)
Abstract Comparative, multi-country research has been underutilised as a means to inform health system development. South-south collaboration has been particularly poor, even though there have been clearly identified benefits of such endeavours. This commentary argues that in a context of HIV/AIDS, the need for regional learning has become even greater. This is because of the regional nature of the problem and the unique challenges that it creates for health systems. We draw on the experience of doing comparative research in South Africa, Tanzania and Zambia, to demonstrate that it can be useful for determining preconditions for the success of health care reforms, for affirming common issues faced by countries in the region, and for developing research capacity. Furthermore, these benefits can be derived by all countries participating in such research, irrespective of differences in capacity or socio-economic development.